An analysis of the breadth and depth of coverage of emerging market countries by commercial patent information sources. (September 2017) - Cole, Nicholas; Ede, Mark; Barcelon-Yang, Cynthia; Harper, Mark; Langeveld, Arjan; Noll, Torsten; Swinkels, Joop; Vang, Guido
Abstract: The Patent Documentation Group (PDG) ONLINE Working Group has undertaken a study comparing different aspects of emerging market country coverage amongst 5 commercial sources of patent information. The sources were compared against the national patent office registers for each of 9 'emerging market' countries, as well as Inpadoc/Espacenet. Coverage was assessed in relation to 25 patent families occupying the pharmaceutical and household or specialty chemical technical domains. In general, vendors were shown to have added value in terms of country coverage over the 'baseline' offered by Inpadoc/Espacenet but to varying degrees fell short of the 'gold standard' offered by registers. These variances were explored, and conclusions and recommendations were shared with the vendors in order to facilitate product development. In a separate effort, observations relating to the design, searchability and reliability of registers were collated and communicated to the PDG IMPACT working group who commonly liaise with WIPO. This has culminated in a proposal being made by the Committee on WIPO Standards (CWS) to set up a task force on standards for (all) patent office registers during 2017.